The effectiveness and costs of intensive stroke rehabilitation and improvements in pa-tient pathway in Finland: a retrospective benchmarking controlled trial - Niko Korpi; Marja Mikkelsson; Unto Häkkinen; Antti Malmivaara (Medical Journals Sweden, 2024)
Objective: To assess the effectiveness and costs of intensive stroke rehabilitation and improvements in patient pathway in the city of Lahti and in Päijät-Häme region compared with other parts in Finland. Design: Retrospective benchmarking controlled trial. Patients: Three cohorts of Finnish community-dwelling patients (n = 94,749, n = 4,184, and n = 105,458) with ischaemic stroke between 2001 and 2019. Methods: This study is based on the PERFECT 2001-2019 database of ischaemic stroke patients. PERFECT indicators describe how the stroke patients recover. The difference-in-difference method was used in the main analysis. Results: Improved stroke rehabilitation in Lahti increased the share of patients discharged home (p = 0.005) and decreased the length of first institutional episode (-4 days, p = 0.006), the share of patients institutionalized (-5.1%, p = 0.001), and the costs of first institutional episode (€-2,085, p < 0.001) compared with the rest of Finland. Discharges to home increased 6.6 percentage points (p = 0.021) in Lahti compared with rest of Päijät-Häme. After 2013, the costs of first institutional episode per patient in Päijät-Häme decreased significantly compared with the rest of Finland (p < 0.001). Conclusion: Investments in intensive stroke rehabilitation and patient pathway seem to provide both faster and better return to home for patients and reduced costs for the healthcare system.